Intelligent and Violent Generation in Early Children through Example Method, Habitation and Advice in the City of Palopo - Sirajuddin, Duriani (Edumaspul: Jurnal Pendidikan, 2023)
This research is a form of early childhood learning in Palopo City in achieving an intelligent and moral Karimah generation, using exemplary methods, habituation, and giving advice to early childhood children in Palopo City. This research aims to provide religious education to young children so that they become intelligent and ethical human beings using a qualitative approach with descriptive methods to obtain more accurate information. Data collection techniques through observation, documentation and interviews, then analyzed using data reduction steps, data presentation and drawing conclusions. The results of the research show that parents as the main educators and the community have the duty to help children by providing religious and moral education by providing direct examples and habituation to carry out worship activities with parents and family and other social activities as well as providing innovative advice in the form of attitudes that reflect Early childhood personality in everyday life.